2021
DOI: 10.1038/s41419-020-03277-0
|View full text |Cite
|
Sign up to set email alerts
|

Indoleamine 2,3-dioxygenase 1 limits hepatic inflammatory cells recruitment and promotes bile duct ligation-induced liver fibrosis

Abstract: Liver fibrosis is a course of chronic liver dysfunction, can develop into cirrhosis and hepatocellular carcinoma. Inflammatory insult owing to pathogenic factors plays a crucial role in the pathogenesis of liver fibrosis. Indoleamine 2,3-dioxygenase 1 (IDO1) can affect the infiltration of immune cells in many pathology processes of diseases, but its role in liver fibrosis has not been elucidated completely. Here, the markedly elevated protein IDO1 in livers was identified, and dendritic cells (DCs) immune-phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…ERO1a has been shown to regulate MDSC induction via GM-CSF and CXCL1/2 secretion (15), whereas IDO1 promotes MDSCs and M2 anti-inflammatory macrophages expansion through tryptophan catabolism (19). Particularly, a recent study presented the overexpression of IDO1 inhibited DC maturation and consequently affected immune cell recruitment in an inflammatory liver model (47). Our study identified a 12-fold reduction in hypoxia signaling, emphasizing the potential of combining ERO1a and IDO1 as hypoxia-driven immune checkpoints.…”
Section: Discussionmentioning
confidence: 50%
“…ERO1a has been shown to regulate MDSC induction via GM-CSF and CXCL1/2 secretion (15), whereas IDO1 promotes MDSCs and M2 anti-inflammatory macrophages expansion through tryptophan catabolism (19). Particularly, a recent study presented the overexpression of IDO1 inhibited DC maturation and consequently affected immune cell recruitment in an inflammatory liver model (47). Our study identified a 12-fold reduction in hypoxia signaling, emphasizing the potential of combining ERO1a and IDO1 as hypoxia-driven immune checkpoints.…”
Section: Discussionmentioning
confidence: 50%
“…IDO, the rate-limiting enzyme in the kynurenine pathway of tryptophan degradation, plays an important role in inflammation. It has been reported that IDO can not only affect the infiltration of immune cells in many pathological disease conditions, including liver fibrosis [ 30 , 31 ], but also further inhibits T cell proliferation and promotes anti-inflammatory macrophage differentiation during MSC therapy [ 29 , 32 ]. Based on the results of our RNA-seq analysis, we hypothesized that IDO was one of the target genes of FSTL1.…”
Section: Resultsmentioning
confidence: 99%
“…Interaction between immune cells resulted in the increased expression of CCL20 in NAFLD fibrosis patients ( 106 ). Indoleamine 2,3-dioxygenase 1 (IDO1), an immunomodulatory enzyme, was highly expressed in choledochotomy (BDL)-induced mice, inhibiting DCs maturation and T cell proliferation from recruiting immune cells and promoting hepatic fibrosis ( 107 ).…”
Section: Liver Cirrhosis Immune Microenvironmentmentioning
confidence: 99%